Meningkatkan Kompetensi Perpajakan Bagi Guru-Guru Akuntansi SMK Di Wilayah Jakarta Timur - Rubiatto Biettant; Licke Bieattant; Liem Yan Sugondo; Eka Pujianthi; Prima Dedi Andrian; Charlie Charlie (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
Taxation as an indispensable science in society, taxation is the biggest revenue in Indonesia. The need for workers who understand taxation continues to increase both at the level of administrative and policy technicians. One of the main competencies in accounting is taxation, because taxation is inseparable from accounting. Accounting teachers must have good competence to be able to transfer their knowledge to students in their schools in an effort to produce graduates that are needed by industry. The tax training that can be delivered this time is about the corporate income tax and fiscal reconciliation report. Community Service Activities (PKM) are carried out by a number of lecturers from the Faculty of Economics and Business of Trisakti University in collaboration with the Development of East Jakarta Education and Vocational Workforce Competency Development (P2KPTK2), held for 2 (two) days on 18-19 July 2019, with participants were accounting teachers with a total of 40 people. Activities in the form of lectures and training.The results and findings of this training activity are known that this activity is very helpful for the teacher management to better understand the calculation of corporate income tax and reporting of fiscal reconciliation reports..